A feasibility study of the burden of disease of atopic dermatitis using a smartphone research application, myEczema - Sheevam Shah, MD; Jacqueline M. Kemp, MD, MS; Joseph C. Kvedar, MD; Lia E. Gracey, MD, PhD (Wolters Kluwer, 2020)
Background: Our understanding of chronic diseases, such as atopic dermatitis (AD), could benefit from the ability to rapidly collect patient-reported, longitudinal data from a large population. Objective: This study aimed to determine whether a smartphone app can be used to collect demographic and longitudinal symptom data and recognize prescribing patterns and affordability of medications to study the burden of AD. Methods: We collected data using the myEczema smartphone app between July 2017 and April 2018. The data were de-identified and analyzed. Results: A total of 519 users (94.2%) completed the initial demographic survey. The majority of users were female (n = 387; 70.2%) and Caucasian (n = 358; 65.0%). A total of 335 users (60.8%) had at least a university degree and were employed (n = 348; 63.1%). A total of 189 users (29.2%) reported difficulty affording their medications, and 363 users (65.9%) took advantage of the itch score recording feature. Finally, 184 users (33.4%) logged their treatments, with the highest number of users (65.2%) listing topical steroids as one of their treatments. Limitations: The operating platform was limited to iPhones, and the results were subject to reporting bias. Conclusion: A smartphone-based research app can be used to rapidly collect patient-reported data to study the burden of AD and to highlight the prescribing patterns and affordability of medications.